Mitral Inflow Obstruction Resulting From a Dilated Coronary Sinus: Role of Intraoperative Transesophageal Echocardiography in Diagnosis and Surgical Repair. Issue 7 (1st April 2017) - Babu, Saravana; Gadhinglajkar, Shrinivas V.; Kumar, Muthu; Sukesan, Subin; Dharan, Baiju S.; Sreedhar, Rupa; Aggarwal, Neelam
Abstract : Mitral inflow obstruction caused by dilated coronary sinus is a rare congenital cardiac anomaly that must be differentiated from other causes of left ventricular inflow obstruction such as cor triatriatum, supramitral membrane, and supramitral ridge, because their surgical repair is different. Although preoperative transthoracic echocardiography is the primary imaging modality for diagnosis, intraoperative transesophageal echocardiography has a higher sensitivity and specificity over transthoracic echocardiography in differentiating these lesions. We report 2 cases of supramitral obstruction where the intraoperative transesophageal echocardiography has refined the preoperative diagnosis and changed the course of surgical repair. Abstract : Supplemental Digital Content is available in the text.